Robust SMES controller design based on inverse additive perturbation for stabilization of interconnected power systems with wind farms - Ngamroo, Issarachai (My University, 2010)
This paper proposes a robust controller design of Superconducting Magnetic Energy Storage (SMES) for stabilization of tie-line power oscillation in the interconnected power systems with wind farms. The inverse additive perturbation model is applied to represent system uncertainties such as several generating and loading conditions, variation of system parameters, wind power fluctuations, etc. The structure of active and reactive power controllers of SMES is the first-order lead-lag compensator. To tune the controller parameters, the optimization problem is formulated based on the enhancement of additive stability margin. The genetic algorithm is used to solve the problem and achieve the controller parameters. Simulation studies in the two-area four-machine interconnected power system with wind farms confirm the robustness of the proposed SMES under various operating conditions. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Inverse additive perturbation; Power system stabilization; Robust control; Superconducting magnetic energy storage; System uncertainties; Wind farms